2015
DOI: 10.1186/s12917-015-0586-3
|View full text |Cite
|
Sign up to set email alerts
|

Ceftiofur hydrochloride affects the humoral and cellular immune response in pigs after vaccination against swine influenza and pseudorabies

Abstract: BackgroundCephalosporins are a class of antibiotics that are active against many Gram-positive and some Gram-negative bacteria. Beyond their antibacterial activity, they are reported to have various immunomodulatory properties. It has been shown that they reduce the secretion of cytokines as well as influence the humoral and cellular immune response.In the field conditions antibiotics are frequently administered at the same time as vaccines in pigs and, in the view of their potential immunomodulatory propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…This may have an unfavourable impact on the immune system response to infection and/or vaccination. This assumption is in accordance with the outcome of earlier studies conducted by Pomorska-Mól et al (21,22) in which therapeutic doses of ceftiofur during vaccination impaired post-vaccinal immune responses in pigs. The negative effect of ceftiofur, florfenicol, and enrofloxacin on B and T cell subsets was also found in another study on chicks, where results were similar to the present study (6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may have an unfavourable impact on the immune system response to infection and/or vaccination. This assumption is in accordance with the outcome of earlier studies conducted by Pomorska-Mól et al (21,22) in which therapeutic doses of ceftiofur during vaccination impaired post-vaccinal immune responses in pigs. The negative effect of ceftiofur, florfenicol, and enrofloxacin on B and T cell subsets was also found in another study on chicks, where results were similar to the present study (6).…”
Section: Discussionsupporting
confidence: 92%
“…In studies by Pomorska-Mól et al (21,22), ceftiofur hydrochloride administered in a recommended dose significantly decreased the production of specific antibodies against Erysipelothrix rhusiopathiae and swine influenza virus (SIV). In pigs treated with ceftiofur and vaccinated at the same time against pseudorabies virus (PRV), a significant delay in the development of the humoral response as well as a reduction in the cellular immune response against PRV were observed (21).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we cannot exclude an indirect role for Gram‐negative bacteraemia on red cell alloimmunisation due to their common association with other modulators. Indeed, suppressed mitogenic B and T lymphocyte responses were observed following administration of antibiotics, including cephalosporins, an antibiotic class frequently used in the treatment of Gram‐negative bacterial infections (Borowski et al , ; Pomorska‐Mol et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the negative effects of DOXY and enrofloxacin on the humoral and/or cellular postvaccinal response after pseudorabies vaccination have been reported (Pomorska-Mol and others 2014, Pomorska-Mol and others 2015a). It has been also found that CEF hydrochloride applied at the same time as vaccines against pseudorabies and swine influenza (attenuated and inactivated, respectively) can negatively affect postvaccinal humoral response in pigs (Pomorska-Mol and others 2015b). …”
Section: Discussionmentioning
confidence: 99%